Collective Health as a Social Science: Reflections on the Possibilities of a Comprehensive Collective Health - Daniel Mendez (GoAcademica Research & Publishing, 2022)
Social interaction employs both verbal and nonverbal language. We investigate the confidence level and brain activity when verbal and facial expressions are inconsistent. Four volunteers stored images of eight individuals whose facial expressions were either agradáveis (smiling) or unfavorable (rejection) sozinhas or in combination with a verbal expression [positive / negative]. As a measure of their trust, the participants were asked to make a donation to the individual in the photograph who was in financial distress. The Visual Analogue Scale was utilized to evaluate positive feelings and self-assurance levels (VAS). After seeing the photos, Event Related Potentials (ERPs) are acquired in 170–240 milliseconds. Standardized low-resolution electromagnetic brain tomography was used to pinpoint brain activity under incongruous situations (sLORETA). The VAS values for the positive condition smile were substantially greater than those for the other conditions (p 0.05). For inconsistency between verbal and facial responses, namely the smiling negative condition, the offer was severely reduced. Under discordant conditions, the parietal lobe was more active on EEG than under congruent conditions. Incongruence [negative smile] evoked less positive emotion, confidence, and offer quantity. Our findings indicate that incongruent sensory input increased activity in the parietal lobe, which may be a result of mentalization.